PENINGKATAN KEMAMPUAN MENGENAL HURUF MELALUI PERMAINAN PANCING HURUF (PANHUF) DI KELOMPOK B TK NEGERI KINTELAN SEMARANG - Salamah, Umi (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
This report is a study on improving the ability to recognize letters in early childhood through the letter fishing game in group B of Kintelan State Kindergarten, namely: (a) What was the condition of the ability to recognize letters before the use of the panhuf game with letter fishing media in Kintelan State Kindergarten? (b) How is the implementation of the learning process to recognize letters using the media fishing game for the children in group B of Kindergarten Kintelan State? (c) How to increase the ability to recognize letters in group B in Kintelan State Kindergarten after applying letter fishing media? with the letter fishing game is to get an idea of ​​the increasing ability of children to recognize letters through playing with letter fishing media. Learning the ability to play letter fishing in group B at Kindergarten Kintelan State is by using supporting tools, namely photos of learning outcomes and observation notes. Increasing knowing letters with panhuf games, 1) can make the atmosphere happy and children become enthusiastic, 2) Learning with letter fishing makes children active in participating in letter recognition activities, 3) letter fishing activities make children interested in playing, 4) Letter fishing learning can improve children in learning to recognize letters at Kintelan State Kindergarten.